2016
DOI: 10.1002/ange.201604741
|View full text |Cite
|
Sign up to set email alerts
|

Pyrenes, Peropyrenes, and Teropyrenes: Synthesis, Structures, and Photophysical Properties

Abstract: The design of ar elatively simple and efficient method to extend the p-conjugation of readily available aromatics in one-dimension is of significant value.I nt his paper,pyrenes,peropyrenes,and teropyrenes were synthesized through ad ouble or quadruple benzannulation reaction of alkynes promoted by Brønsted acid. This novel method does not involve cyclodehydrogenation (oxidative aryl-aryl coupling) to arrive at the newly incorporated large arene moieties. All of the target compounds were synthesized in moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…A conceptual synthetic strategy toward cycloarenes is to build up initially, the macrocyclic oligo(m-phenylene) precursors carrying alkyne/alkene groups on the outer periphery, followed by Brønsted acid or Lewis acid-catalyzed cyclization reaction. [15][16][17][18][19][20][21] Our initial effort of using acid-catalyzed cyclization of alkyne precursors was not successful after many attempts. Fortunately, we found that the Bi(OTf) 3 -catalyzed cyclization reaction of vinyl ether developed by Murai et al 22 was efficient (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…A conceptual synthetic strategy toward cycloarenes is to build up initially, the macrocyclic oligo(m-phenylene) precursors carrying alkyne/alkene groups on the outer periphery, followed by Brønsted acid or Lewis acid-catalyzed cyclization reaction. [15][16][17][18][19][20][21] Our initial effort of using acid-catalyzed cyclization of alkyne precursors was not successful after many attempts. Fortunately, we found that the Bi(OTf) 3 -catalyzed cyclization reaction of vinyl ether developed by Murai et al 22 was efficient (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…The triazapyrene skeleton in 3a contains planar structures. 10,11 The dihedral angles between the triazapyrene moiety and benzene rings are 51° and 59°. Triazapyrene 3a formed head-to-tail dimers with the distance of 3.40 Å between least-squares planes of the triazapyrene core.…”
Section: Resultsmentioning
confidence: 99%
“…[28] A more convenient protocol was developed by Chalifoux and co-workers who built up the peropyrene scaffold by acid mediated intramolecular benzannulation of internal alkynes (Scheme 2a). [29][30][31] This approach enables the functionalization of the bay positions of peropyrene and leads therefore to twisted peropyrens with up to 18°out of plane twist angle and axial chirality. [30] The most twisted representative is a tetranaphthyl annulated peropyrene built up via oxidative Scholl dehydrogenation of a tetranaphthyl-diphenylbenzene precursor reported by the group of Miao (Scheme 2b) [32] and later extended with pyrene functionalities by Feng.…”
Section: Introductionmentioning
confidence: 99%